A Game-Playing Approach to Interviewing Children About Loneliness: Negotiating Meaning, Distributing Power, and Establishing Trust (Alberta Journal of Educational Research, 2006)
The new paradigm of studying childhood that has emerged in the past 15 years has significant implications for rethinking research with children. This article examines some methodological and ethical issues related to the role and responsibility of a researcher in the process of designing, structuring, and conducting research on childhood experiences and the role of children in such research. The main conceptual points are illustrated through examples from the process of developing and employing a game-playing approach to initiating conversations with young children about loneliness. Excerpts from a tape-recorded game-playing session with a 10-year-old child are used to illustrate how the approach facilitates negotiating meaning, distributing power, and establishing trust between the interviewer and the interviewee. The role of the game-playing approach as a research tool for involving children in the research process is examined.